Mass spectrometry in combination with a chiral column and multichannel-MRM allows comprehensive analysis of glycosphingolipid molecular species from mouse brain. (April 2020) - Fujiwara, Yuko; Hama, Kotaro; Yokoyama, Kazuaki
Abstract: Glycosphingolipids (GSLs) exist exclusively in the outer leaflet of plasma membrane in mammalian cells and have diverse structures including different classes of sugars and various molecular species of ceramide moieties. Establishing methods that measure each molecular species in GSL classes should aid functional characterization of GSLs and reveal details about the mechanism of pathogenesis in glycosphingolipidoses. Using an IF-3 chiral column that has never been used for lipid analyses, we developed a liquid chromatography-mass spectrometry (LC-MS) method to separate various GSLs based on sugar and ceramide moieties. To examine GSLs in detail a multichannel-multiple reaction monitoring (multichannel-MRM) mode was used and covered a range of 500–2000 Da. Common fragment ions detected with higher collision energy in the positive ion mode were m/z 264 and 292, and are derived from d18:1 and d20:1 ions, respectively. Both species were used as product ions in the multichannel-MRM for the simultaneous measurement of neutral GSLs, gangliosides and sulfatides. Comprehensive analysis of GSLs in mouse brain using this method revealed that for gangliosides and LacCer, d18:1–C18:0 and d20:1–C18:0 were the major molecular species, whereas d18:1–C24:0 and d18:1–C24:1 were the major molecular species of sulfatides. The results revealed a diverse GSL fatty acid profile. In conclusion, by combining IF-3 chiral column and the multichannel-MRM method various molecular species of GSLs were detected successfully, and a metabolomics approach based on this LC-MS method should facilitate functional analysis of GSLs and the discovery of early biomarkers of glycosphingolipidoses at the molecular level. Graphical abstract: Image 1 Highlights: A novel LC-MS method was used to detect various molecular species of GSLs. An IF-3 chiral column was used to separate GSLs. Separation was based on the differences of carbohydrate chain and ceramide moiety. Multichannel-MRM by detecting a LCB of GSL in the positive ion mode was used. The LC-MS method detected various GSL classes from mouse brain.